Change in the Educational Scheme From a Traditional to a Redesigned System: Case Study of the Management Department at the ITESM-Campus Monterrey - Ramirez, Jacobo; Flores, Miguel (Proceedings of the International Conference on Networked Learning, 2004)
The objective of this paper is to present the implications of the change in the educational system at the ITESM. The main objective of this educational system’s change is to incorporate different didactic techniques together with a different infrastructure. Two hundred and fifty undergraduate students answered a questionnaire and twenty members of the academic staff were interviewed. One of the major conclusions found from the students and academic staff is that the education system is a changing process which implies a transformation of the profiles in both academics and students. Thus, educational technology might be essential in the current changing environment.